Growth of a cohort of very low birth weight and preterm infants born at a single tertiary health care center in South Africa - Michaelis, Isabel Alexandra; Krägeloh-Mann, Ingeborg; Mazinu, Mikateko; Jordaan, Esme (Frontiers in Pediatrics, 2023)
Background Very low birth weight (VLBW) and extremely low birth weight (ELBW) infants are known to be at high risk of growth failure and developmental delay later in life. The majority of those infants are born in low and middle income countries. Aim Growth monitoring in a cohort of infants born with a VLBW up to 18 months corrected age was conducted in a low resource setting tertiary hospital. Methods In this prospective cohort study, 173 infants with a birth weight below 1,501 g admitted within their first 24 h of life were recruited and the 115 surviving until discharged were asked to follow up at 1, 3, 6, 12 and 18 months. Weight, height and head circumferences were recorded and plotted on WHO Z-score growth charts. Results Of the 115 discharged infants 89 were followed up at any given follow-up point (1, 3, 6, 12 and/or 18 months). By 12 months of corrected age another 15 infants had demised (13.0%). The infants' trends in weight-for-age z-scores (WAZ) for corrected age was on average below the norm up to 12 months (average estimated z-score at 12 months = −0.44; 95% CI, −0.77 to −0.11), but had reached a normal range on average at 18 months = −0.24; 95% CI, −0.65 to 0.19) with no overall difference in WAZ scores weight between males and female' infants (p > 0.7). Similar results were seen for height at 12 months corrected age with height-for-age z-scores (HAZ) of the study subjects being within normal limits (−0.24; 95% CI, −0.63 to 0.14). The mean head circumference z-scores (HCZ) initially plotted below −1.5 standard deviations (S.D.), but after 6 months the z-scores were within normal limits (mean z-score at 7 months = −0.19; 95% CI, −0.45 to 0.06). Conclusion Weight gain, length and head circumferences in infants with VLBW discharged showed a catch-up growth within the first 6–18 months of corrected age, with head circumference recovering best. This confirms findings in other studies on a global scale, which may be reassuring for health systems such as those in South Africa with a high burden of children born with low birth weights.